The Artist as a social critic/visionary (The Metropolitan Museum seminars in art, 1986)
Deals with the role of the artist in society, showing how he has expressed ideas on human relationships protested against vice and injustice, and commented on man's follies or achievements. Considers the artist as poet, and explains that he may base his visionary paintings on the world around him or fabricate new worlds.